INFLUENCE OF CONNECTIVE TISSUE DYSPLASIA ON THE COURSE OF GLOMERULONEFRITIS IN CHILDREN - Mirrahimova Maktuba Khabibullaevna; Agzamkhodzhaeva Nasiba Saidmagrufovna; Ikromova Shakhnoza Nazimovna (Galaxy International Interdisciplinary Research Journal, 2022)
Glomerulonephritis is a multifactorial disease and is characterized by a high rate of increase in the incidence and disability of the child population in modern populations [1,3]. Despite extensive study, the development and progression of glomerulonephritis (GN) remains one of the leading problems in nephrology. In recent years, special attention has been paid to children who have signs of systemic changes in various organs associated with the peculiarities of metabolism and the structure of the connective tissue, which clinically manifest themselves as a complex of symptoms and are referred to in the literature as connective tissue dysplasia (CTD) [2,7].